Endogenous dynamics of institutional change. (February 2017) - DellaPosta, Daniel; Nee, Victor; Opper, Sonja
A parsimonious set of mechanisms explains how and under which conditions behavioral deviations build into cascades that reshape institutional frameworks from the bottom up, even if institutional innovations initially conflict with the legally codified rules of the game. Specifically, we argue that this type of endogenous institutional change emerges from an interplay between three factors: the utility gain agents associate with decoupling from institutional equilibria, positive externalities derived from similar decoupling among one's neighbors, and accommodation by state actors. Where endogenous institutional change driven by societal action is sufficiently robust, it can induce political actors to accommodate and eventually to legitimize institutional innovations from below. We provide empirical illustrations of our theory in two disparate institutional contexts—the rise of private manufacturing in the Yangzi delta region of China since 1978, focusing on two municipalities in that region, and the diffusion of gay bars in San Francisco in the 1960s and 1970s. We validate our theory with an agent-based simulation.